Faktor Pemilihan Bingkai Kacamata Untuk Lensa Progresif Pada Pasien Anomali Refraksi Yang Disertai Pesbiopia - Zakaria Efendi; Wahyu Budiana; Murni Marlina Simarmata (Akademi Refraksi Optisi dan Optometry Gapopin, 2021)
Presbyopia is a condition of the eye that loses the ability to focus gradually, to see objects at close range. Presbyopia develops gradually, so someone sometimes just realizes the symptoms after passing the age of 40 years. Glasses are a tool to improve one's visual acuity. The choice of eyeglass frames for progressive lens use for presbyopia is very necessary to prevent inconvenience in using progressive lenses. A progressive lens is a lens where the strength of the lens gradually increases from the far zone, through the corridor to the near zone. In order for progressive lenses to provide optimal performance, first of all, the selection of eyeglass frames is right for the comfort of glasses wearers.